Atypical conjunctival sporotrichosis secondary to Mooren’s ulcer: a case report - Qing Su; He Dong; Lin Cui; Lijun Zhang (BMC Infectious Diseases)
Abstract Background Conjunctival sporotrichosis is a rare fungal infection, typically presenting as granulomatous lesions. Its manifestations can be atypical, particularly in immunosuppressed patients. Here, we present a rare case of a Mooren’s ulcer patient with bulbar conjunctival Sporotrichosis presenting as a salmon-pink tumor. Case presentation A 61-year-old with a history of Mooren’s ulcer and corneal transplantation was diagnosed with conjunctival Sporotrichosis in the left eye. Slit-lamp examination showed conjunctival congestion and edema with a salmon-pink appearance, accompanied by nodules looking like “bread crumbs” scattered under the conjunctiva. After partial tumor resection, histopathology and immunofluorescence staining suggested fungal infection with squamous epithelial hyperplasia. Microbiological testing (DNA) confirmed Sporothrix schenckii as the pathogen. The conjunctival mass resolved without recurrence after local and systemic anti-fungal medicine treatment. Despite the progression of Mooren’s ulcers, which further dissolved and perforated during treatment, aggressive management helped the patient retain some vision. Conclusion Immunosuppression, such as steroids and tacrolimus eyedrops, may predispose patients to opportunistic infections like sporotrichosis. Oral itraconazole, combined with subconjunctival and topical antifungal therapy, effectively treat severe Sporothrix conjunctivitis. Future studies should explore the balance between antifungal and immunosuppressive therapies to manage coexisting conditions like Mooren’s ulcer while curing fungal infections.